Menjaga Motivasi Belajar dengan Re-kontruksi Metode Pembelajaran: Sebuah Kompensasi atas Minimnya Fasilitas Sekolah - Nurzaima, Nurzaima; Hildayanti, Hildayanti; Arfin, Arfin; Nasir, Nasir; Juhadira, Juhadira; Jaya, Asman (LP3M, Universitas Muhammadiyah Kendari, 2023)
In elementary schools, maintaining students' learning motivation through the reconstruction of teaching methods is essential. The rationale for this research is to identify the negative impact of the lack of school facilities on students' learning motivation and to develop effective teaching methods to compensate for these limitations. The research steps include problem identification, planning, implementation, and evaluation of the reconstructed teaching methods. Data collection is carried out through observation, interviews, and student learning assessments. The results of this research show that the reconstruction of teaching methods through creative utilization of available resources can enhance students' learning motivation. Students respond positively to a more interactive learning approach, including the use of easily accessible teaching materials and project-based learning. This research provides a significant contribution in the context of elementary education in schools with limited facilities by demonstrating that creativity in utilizing existing resources can overcome these constraints and maintain students' learning motivation. Recommendations for future research include observing the long-term impact of these teaching methods and adapting them to other elementary school conditions with similar facility limitations.